Context influences the motivation for stereotypic and repetitive behaviour in children diagnosed with intellectual disability with and without Autism - Joosten, Annette; Bundy, A.; Einfeld, S. (Wiley-Blackwell Publishing Ltd., 2012)
Background: Children are motivated to engage in stereotypic and repetitive behaviours for a number of reasons. Their motivation seems to change according to context, but little empirical evidence supports that observation. Interventions designed to reduce the behaviours may be improved by an increased understanding of the interaction between motivation and context. Method: Using Rasch analysis, we analysed data describing stereotypic behaviours from 279 Revised Motivation Assessment Scales (MAS:R). Data were gathered from two groups of children: Group 1 with intellectual disability (n = 37) and Group 2 with both intellectual disability and autism (n = 37). We examined behaviours in three contexts: free time, transition and while engaged in tasks. MAS:R distinguishes two intrinsic motivators: enhanced sensation and decreased anxiety and three extrinsic motivators: seeking attention or objects or escape. Results: Significant differences in motivators were observed during free time and transition. No one motivator predominated while children were engaged in tasks. For both groups, sensory enhancement was a more likely motivator in free time and anxiety reduction was a more likely motivator during transition. Transition was the context most likely to influence extrinsic motivators, but there were significant differences between the groups. Conclusions: Context influences the motivation for stereotyped and repetitive behaviours. Transition has a particularly powerful effect.